The diterpene Manool extracted from Salvia tingitana lowers free radical production in retinal rod outer segments by inhibiting the extramitochondrial F1Fo ATP synthase. (20th January 2021) - Ravera, Silvia; Esposito, Alfonso; Degan, Paolo; Caicci, Federico; Manni, Lucia; Liguori, Anna; Bisio, Angela; Iobbi, Valeria; Schito, Anna; Traverso, Carlo Enrico; Panfoli, Isabella
Abstract : Uncontrolled oxidative stress production, especially in the outer retina is one of the causes of retinal degenerations. Mitochondria are considered the principal source of oxidative stress. However, a Reactive Oxygen Intermediates (ROI) production in the retinal photoreceptor layer seems to depend also on the expression of an extramitochondrial oxidative phosphorylation (OxPhos) machinery in the rod outer segments (OS). In fact, OS conduct aerobic metabolism, producing ATP through oxygen consumption, although it is devoid of mitochondria. As diterpenes display an antioxidant effect, we have evaluated the effect Manool, extracted from Salvia tingitana, on the extramitochondrial OxPhos and the ROI production in the retinal rod OS. Results confirm that the OxPhos machinery is ectopically expressed in the OS and that F1 Fo ‐ATP synthase is a target of Manool, which inhibited the OS ATP synthesis, binding the F1 moiety with high affinity, as analysed by molecular docking. Moreover, the overall slowdown of OxPhos metabolism reduced the ROI production elicited in the OS by light exposure, in vitro. In conclusion, data are consistent with the antioxidant properties of Salvia spp., suggesting its ability to lower oxidative stress production, a primary risk factor for degenerative retinal diseases. Significance of the study: Here we show that Manool, a diterpene extracted from Salvia tingitana has the potential to lower the free radical production by light‐exposed rod outer segments in vitro, by specifically targeting the rod OS F1 Fo ‐ATP synthase belonging to the extramitochondrial OxPhos expressed on the disk membrane. The chosen experimental model allowed to show that the rod OS is a primary producer of oxidative stress linked to the pathogenesis of degenerative retinal diseases. Data are also consistent with the antioxidant and anti‐inflammatory action of Salvia spp., suggesting a beneficial effect also in vivo.